Evaluation of dental pulp stem cells behavior after odontogenic differentiation induction by three different bioactive materials on two different scaffolds - Basma Ahmed; Mai H. Ragab; Rania A. Galhom; Hayam Y. Hassan (BMC, 2023)
Abstract Background To study the odontogenic potential of dental pulp stem cells (DPSCs) after induction with three different bioactive materials: activa bioactive (base/liner) (AB), TheraCal LC (TC), and mineral trioxide aggregate (MTA), when combined with two different types of scaffolds. Methods DPSCs were isolated from freshly extracted premolars of young orthodontic patients, cultured, expanded to passage 4 (P), and characterized by flow cytometric analysis. DPSCs were seeded onto two scaffolds in contact with different materials (AB, TC, and MTA). The first scaffold contained polycaprolactone-nano-chitosan and synthetic hydroxyapatite (PCL-NC-HA), whereas the second scaffold contained polycaprolactone-nano-chitosan and synthetic Mg-substituted hydroxyapatite (PCL-NC-Mg-HA). DPSC viability and proliferation were evaluated at various time points. To assess odontoblastic differentiation, gene expression analysis of dentin sialophosphoprotein (DSPP) by quantitative real-time polymerase chain reaction (qRT-PCR) and morphological changes in cells were performed using inverted microscope phase contrast images and scanning electron microscopy. The fold-change in DSPP between subgroups was compared using a one-way ANOVA. Tukey's test was used to compare the fold-change in DSPP between the two subgroups in multiple comparisons, and P was set at p < 0.05. Results DSPP expression was significantly higher in the PCL-NC-Mg-HA group than in the PCL-NC-HA group, and scanning electron microscopy revealed a strong attachment of odontoblast-like cells to the scaffold that had a stronger odontogenic differentiation effect on DPSCs than the scaffold that did not contain magnesium. MTA has a significantly higher odontogenic differentiation effect on cultured DPSCs than AB or TC does. The combination of scaffolds and bioactive materials improves DPSCs induction in odontoblast-like cells. Conclusions The PCL-NC-Mg-HA scaffold showed better odontogenic differentiation effects on cultured DPSCs. Compared to AB and TC, MTA is the most effective bioactive material for inducing the odontogenic differentiation of cultured DPSCs.